2016
DOI: 10.1111/asj.12673
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lactic acid bacterial strains for meat fermentation and the product's antioxidant and angiotensin‐I‐converting‐enzyme inhibitory activities

Abstract: In the lactic acid bacteria (LAB) strains screened from our LAB collection, Lactobacillus (L.) sakei strain no. 23 and L. curvatus strain no. 28 degraded meat protein and tolerated salt and nitrite in vitro. Fermented sausages inoculated strains no. 23 and no. 28 showed not only favorable increases in viable LAB counts and reduced pH, but also the degradation of meat protein. The sausages fermented with these strains showed significantly higher antioxidant activity than those without LAB or fermented by each L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…The digested samples were centrifuged at 10,000× g for 15 min, and the supernatants were subjected to an ACE inhibitory assay. ACE inhibitory activity was measured using a previously reported method [ 24 , 25 ]. ACE, a dipeptidyl carboxypeptidase (EC 3.4.15.1) extracted from rabbit lung, was obtained from Sigma Chemical Co. (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The digested samples were centrifuged at 10,000× g for 15 min, and the supernatants were subjected to an ACE inhibitory assay. ACE inhibitory activity was measured using a previously reported method [ 24 , 25 ]. ACE, a dipeptidyl carboxypeptidase (EC 3.4.15.1) extracted from rabbit lung, was obtained from Sigma Chemical Co. (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…There were no statistically significant differences between the samples after 270 days of ageing (p > 0.05). Takeda et al (2017) also reported that the ACE inhibitory activity of products fermented with LAB was higher than the activity in those fermented without LAB.…”
Section: Assessment Of Ace Inhibitory Activity After Simulated Gastromentioning
confidence: 96%
“…For example, allochthonous strains showed delayed growth phases during tomato fermentation compared to selected autochthonous strains from tomatoes [12]. Some studies have shown that total antioxidant and ACE inhibition activities were different, depending on the lactic acid bacteria (LAB) strains [13]. Lactobacillus plantarum, Lactobacillus brevis, and Pediococcus pentosaceus were the main LAB strains isolated from spontaneously-fermented tomatoes [4].…”
Section: Introductionmentioning
confidence: 99%